Miraculous transformation of human being through returning to the Qur’an - Osmani, Noor Mohammad (2018)
“Return to the Qur’an, and transform your life”. This is a universal fact for today’s devastated humanity. Humanity is suffering from religious bankruptcy, moral decay, political subjugation, economic exploitation and social degeneration. The only panacea for all humanity is the one that was revealed by the Creator of humanity, Almighty Allah (SWT). The Qur’an changed the Arab people of Jahiliyyah into ideal human generation for all time. A heart touching recitation of the Qur’an by the Prophet (PBUH) was all it took to melt the hearts of the Arabs. In the current scenario as well, most of the people who accepted the universal religion of humanity, Islam, as prescribed by Allah (SWT), was done after getting in contact with the Qur’an. Allah swt guides the one He loves through this Qur’an. This changes a non-believer into a staunch supporter of Islam. It also transforms a believer in name into a believer in practice. It guarantees peace, tranquility, shifa, hidayah for its devoted readers and followers. If one reads the Qur’an, and does not find the Qur’an addressing him, he is not reading the Qur’an in its true sense. It is the ultimate and Final Book for humanity to live till the Day of Judgment. It guarantees the love of Allah for those who love the Qur’an. It takes away his worries, sufferings and anxieties, and instead guarantees a happy peaceful life in this world and in Hereafter. This research would primarily derive Qur’anic ayat that reflect on human transformation from evil to virtuous life. It will also look into the relevant ahadith of the Prophet (PBUH) and the practical demonstrations of the lives of the Companions of the Prophet, the first addressees of the Qur’an, who lived with the Qur’an and by the Qur’an, which in turn made them ideal generation of all time. The Qur’an in fact turned them into an amazing, miraculous generation of all time, the like of which the humanity failed to produce in the course of history.